Inequality of Education for Girls Reflected in Malala Yousafzai & Christina Lamb's I am Malala (2013) Memoir: A Feminist Approach - Pamungkas, Putri Adhi; , Dr. Phil Dewi Chandraningrum S.Pd M.Ed; , Titis Setyabudi SS, M. Hum (2015)
The major problem in this study is how the inequality of education for girls is reflected in "I am Malala" memoir. The objectives of this study are to analyze this I am Malala (2013) memoir based on its structural elements and to describe the inequality of education for girl based on the feminist analysis that conducts feminist perpectives; women position, women role, women participation and women rights. The object of this study is I am Malala (2013) memoir by Malala Yousafzai & Christina Lamb. This study uses qualitative research. In this method, there are two types of data source namely primary and secondary data. The primary data source is I am Malala memoir and the secondary data source is the other materials from several sources that related to the study. The result of the study shows that there is close relation between the memoir and social life in Pakistan about inequality of education for girls. Malala Yousafzai & Christina Lamb want to show the real condition of education, and they want to show that education is important aspect for human life, and there should not be gender inequality in education because education is for boys and girls.